Effectiveness of Program for Older People's Health Literacy on Drug and Health Products: Northeast of Thailand - Tharinee Srisaknok; Chanuttha Ploylearmsang; Ranee Wongkongdech (Wolters Kluwer Medknow Publications, 2024)
Introduction: A health literacy promotion program in drugs and health products was collaboratively developed and evaluated for effectiveness by researchers and stakeholders. Methods: A Solomon four-group randomized study was conducted in 2022. The participants were people aged ≥60 years enrolled at senior schools in Northeast Thailand. One hundred and eighty older people were randomly selected using multistage sampling and allocated into four groups, 45 members. The designed program covers six skills: access to health information, cognition, communication, decision-making, media literacy, and self-management. ANOVA and t-test were used. Results: One hundred percent response rate, participants of the program (Group 1) showed a significant improvement (pre-post) of 62.2% in their health literacy in drugs and health products use (151.54 ± 37.88, 245.73 ± 9.33, P < 0.001). Group 3, older people who joined the program with posttest only showed health literacy of 248.67 ± 11.54. In contrast, Group 2 and Group 4 with no program showed less health literacy of 149.02 ± 32.08 and 145.22 ± 34.14, respectively. On each item, the older people with the program consistently scored significantly higher across all domains (P < 0.001). The average score was 247.20 ± 10.54, which showed a high level of health literacy (≥75%). Among areas, decision-making skills revealed the highest score of 45.97 ± 1.81 out of 50. The overall satisfaction score on the program was 47.60 ± 1.50. Conclusion: The program demonstrated its effectiveness in improving the older population's health literacy regarding drug and health product use. It holds potential as a strategy to encourage older people to rational drug use. Participants expressed a significant satisfaction with the program, recommended for the broader Thai older people community.